2021
DOI: 10.1038/s41598-020-79572-9
|View full text |Cite
|
Sign up to set email alerts
|

Negative index metamaterial through multi-wave interactions: numerical proof of the concept of low-frequency Lamb-wave multiplexing

Abstract: We study numerically the potential of a multimodal elastic metamaterial to filter and guide Lamb waves in a plate. Using a sub-wavelength array of elongated beams attached to the plate, and combining the coupling effects of the longitudinal and flexural motion of these resonators, we create narrow transmission bands at the flexural resonances of the beams inside the wide frequency bandgap induced by their longitudinal resonance. The diameter of the beams becomes the tuning parameter for selection of the flexur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A rough estimation with azimuthal averaging of the radiation circles highlights a decrease in the wavenumber over a 60 Hz frequency bandwidth. We estimate around -3.3 m/s at 2150 Hz the group velocity, which is in the same order of magnitude ($-2 m/s) as recently publish numerical simulation on a similar setup (Lott et al, 2021). The fluctuations on the radiation circle in the measurement in Fig.…”
Section: Leakage At Flexural Resonances and Negative Index Materialssupporting
confidence: 76%
See 1 more Smart Citation
“…A rough estimation with azimuthal averaging of the radiation circles highlights a decrease in the wavenumber over a 60 Hz frequency bandwidth. We estimate around -3.3 m/s at 2150 Hz the group velocity, which is in the same order of magnitude ($-2 m/s) as recently publish numerical simulation on a similar setup (Lott et al, 2021). The fluctuations on the radiation circle in the measurement in Fig.…”
Section: Leakage At Flexural Resonances and Negative Index Materialssupporting
confidence: 76%
“…6, panel 3, a-c, suggests a large attenuation effect in the plate wave propagation. Recent numerical studies have shown that the transmission of energy through the flexural resonance motion is highly sensitive to small amounts of disorder in the beams positions (Lott et al, 2021). We conclude that the loss is due to strong scattering effects coming from the imperfect position of the beams in our experimental realization of the square lattice metasurface, and not to intrinsic damping properties of the material.…”
Section: Leakage At Flexural Resonances and Negative Index Materialsmentioning
confidence: 58%
“…In Ref. 26 , there is a negative index metamaterial made up of extended beams enclosed to a plate. A 3 dimensions acoustic MTM is examined in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using a sub-wavelength array of beams attached to the plate, Lott [17] created a narrow transmission bands at the flexural resonances of the beams inside the wide frequency bandgap. A metamaterial terahertz biosensor, which has two resonant absorption frequencies, was represented by Li [18] for fast and label-free identification of early-stage cervical cancerous tissues.…”
Section: Introductionmentioning
confidence: 99%